PENGARUH PUPUK KANDANG DAN TANAH BERTEKSTUR LIAT TERHADAP SIFAT KIMIA TANAH TAILING SERTA RESPON TANAMAN JAGUNG MANIS (Zea mays Saccharata) - Mei Cen Trisnady; Tommy D. Sondakh; Rafli I. Kawulusan (Universitas Sam Ratulangi, 2017)
ABSTRACTThe effect mixing of chicken manure and clayed soils (soil colloids) into ex-mining soils (tailings) on soil chemical properties and growth of sweet corn plants were the objective of this study. Tailings and the clay soils were taken from Tatelu Village of Dimembe Subdistrict and from Paniki Mapanget Subdistrict, respectively. This field research was conducted in Tara-tara II Subdistrict Tomohon West, District of Tomohon. Soil analyses were conducted in Soil Chemistry and Soil Fertilizer and in Soil Physics and Soil Conservation Laboratory at Soil Department, Agriculture Faculty UNSRAT Manado. A completely randomized design consisting of 7 treatments in 4 replicates is utilized in experiment using a 30 kg polybags. The results showed that mixing of clay-textured soil and manure on tailings gave significant effect on soil cation exchange capacity, soil P-available, K-available, corn dry weights, and corn cob weights. However, mixing materials have no significant effect on pH, C-organic content, and total N-content. The best combination mixing of materials is 40 persent clay textured soil and 30 tons of chicken manure and tailings.Keywords: Tailings, Clay Textured Soil and Chicken Manure